Basic Genetics - Weaver, Robert Franklin, Hedrick, Philip W. (Wm. C. Brown Publishers, 1995)
Provides a balanced coverage of clinical and molecular genetics. Experimental highlights and extensive use of learning aids are used throughout. After a broad introduction to the topic, the book is divided into 3 parts - Mendelian genetics, molecular genetics and population genetics.